2023
DOI: 10.1038/s41419-023-05922-w
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection and COVID-19 vaccination in cancer patients undergoing immune checkpoint inhibitors

Abstract: Cancer patients are susceptible to severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Different antitumor treatments have attracted wide attention in the context of coronavirus disease 2019 (COVID-19), especially immune checkpoint inhibitors (ICIs) that have revolutionized oncology changes. It may also have protective and therapeutic roles in viral infections. In this article, we collected 26 cases of SARS-CoV-2 infection during ICIs therapy and 13 related to COVID-19 vaccination from Pubmed, EMBASE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…COVID-19 vaccination recommendations were initially released from national and international Oncology scientific societies on theoretical grounds and based on consensus among peers [2]. Subsequent studies have shown that vaccination is safe and effective in protecting cancer patients from hospitalization and death deriving from COVID-19 infection [3][4][5]. In Italy, population studies conducted in the Friuli-Venezia Giulia region and Reggio Emilia province show that the risk of death of cancer patients who did not undergo anti-SARS-CoV-2 vaccination is 2-3 fold higher than that of their vaccinated counterpart [6], in line with European data from the OnCovid registry study [7].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 vaccination recommendations were initially released from national and international Oncology scientific societies on theoretical grounds and based on consensus among peers [2]. Subsequent studies have shown that vaccination is safe and effective in protecting cancer patients from hospitalization and death deriving from COVID-19 infection [3][4][5]. In Italy, population studies conducted in the Friuli-Venezia Giulia region and Reggio Emilia province show that the risk of death of cancer patients who did not undergo anti-SARS-CoV-2 vaccination is 2-3 fold higher than that of their vaccinated counterpart [6], in line with European data from the OnCovid registry study [7].…”
Section: Introductionmentioning
confidence: 99%
“…An increase in incidence of myocarditis and myositis post-ICB has been noted by others since the beginning of the COVID-19 pandemic, 30 31 and it is possible similar cases with this unusual clinical presentation have been overlooked. Further, multiple case series describing other irAEs have been recently published as summarized in a recent review 32 and toxicity has been noted postvaccination as well as following natural infection. 33 Further, an overall increase in incidence of autoimmune diseases following the pandemic has been described.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous reports suggest that host immune status and external factors such as COVID-19 vaccinations ( 7 ), corticosteroids ( 8 ), and antibiotics/probiotics ( 9 ) affect anti-cancer immune systems by stimulating or suppressing immune cells. It is well known that diet and lifestyle also affect immune status, these potentially influence the efficacy for ICI therapy ( 10 ).…”
Section: Discussionmentioning
confidence: 99%